2008
DOI: 10.1177/014556130808701107
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Otomycosis in an Immunocompromised Patient

Abstract: Aspergillus niger, an opportunistic filamentousfungus, wasidentified asthecause ofchronic unilateralotomycosis in a 55-year old, immunocompromised man who had been unresponsive toa varietyof treatment regimens. The patient presented with intermittent otalgia and otorrhea and with a perforation ofhis left tympanic membrane. A niger wasidentified inaculturespecimen obtainedfrom the patient'sleftear canal. In immunocompromised patients, it isimportant that the treatment ofotomycosis beprompt and vigorous, to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 12 publications
5
26
0
3
Order By: Relevance
“…Otolaryngologists should remain alert for detection of otomycosis and should consider obtaining culture when this disease is suspected. The findings in this study are in general agreement with the findings observed by earlier workers like Rutt et al [35] and Ozcan et al [36].…”
Section: Discussionsupporting
confidence: 94%
“…Otolaryngologists should remain alert for detection of otomycosis and should consider obtaining culture when this disease is suspected. The findings in this study are in general agreement with the findings observed by earlier workers like Rutt et al [35] and Ozcan et al [36].…”
Section: Discussionsupporting
confidence: 94%
“…Tympanic membrane perforation may occur as a complication of otomycosis that starts in an ear with an intact ear drum. 3 In the study by Rama Kumar, the incidence of tympanic membrane perforation in otomycosis was found to be 11%. 15 He also stated that perforations were more common with otomycosis caused by C albicans.…”
Section: Discussionmentioning
confidence: 99%
“…1 In immunocompromised patients, treatment of otomycosis should be vigorous to prevent complications such as hearing loss and invasive temporal bone infection. 3 We conducted a comparative clinical study involving 50 immunocompetent and 50 immunocompromised patients with otomycosis. Clinical presentation, predisposing factors, mycologic profile, and treatment outcomes were compared.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of perforation has been attributed to mycotic thrombosis of the tympanic membrane blood vessels resulting in avascular necrosis of tympanic membrane 5,17. There may not be any clinical features predictive of tympanic membrane perforation.…”
Section: Introductionmentioning
confidence: 99%